An analysis of heat-related illnesses in children due to immoderate temperatures - Agrawal, Amit; Agrawal, Rashmi (Indian Journal of Child Health, 2024)
Soaring temperatures, as a result of climate change, is impacting all beings across the globe. This has led to multiple illnesses and emergency room visits, during extreme temperatures, especially summers. The most vulnerable to scorching heat are infants, children and adolescents along with the elderly. Heat-related illnesses (HRIs) may range from minor forms, such as prickly heat, to severe, life-threatening conditions such as heatstroke. Pediatricians need to be aware of the varying physiologies and behaviors the children might present as a result of HRI and predisposing factors that may put them further at risk. Although the pathophysiology of HRI is understood, the scope of pharmacotherapy to treat them is limited. Currently, prevention is the best course of action against HRIs. Thus, the escalating average temperatures and challenges, posed by climate change, demand a review of the existing preventive and treatment strategies for HRIs. This article hence, attempts to compile the different kinds of HRIs along with their pathophysiology, causes, and detection and how they can be prevented and treated among children.